A prolific catalyst for dehydrogenation of neat formic acid - Jeff Joseph A. Celaje (Nature Portfolio, 2016)
Formic acid is a promising energy carrier for on-demand hydrogen generation. Here, the authors present a robust, reusable iridium catalyst that enables hydrogen release from neat formic acid under mild conditions and in the presence of air.